Assessing the Impacts of the Road Safety Remuneration System in Australia - Deighton-Smith, Rex (International Transport Forum Discussion Papers, 2019)
This paper is a case study of the application of Regulatory Impact Assessment (RIA) to the legislation that established Australia's Road Safety Remuneration System. It highlights two considerations: first, how RIA can provide important information to policy makers, despite complexity and a lack of data preventing a full cost benefit analysis. Second, that RIA can only be influential when adopted as part of a well-designed and fully functioning process, particularly where the policy environment is a politically charged one